High-entropy alloy coated single crystal nickel-rich cobalt-free positive electrode material and preparation method thereof

The preparation of a high-entropy alloy coated single-crystal nickel-rich cobalt-free cathode material is simplified by solid-phase sintering method, solving the problems of high cost, low safety and complex preparation in the prior art, and achieving high conductivity and excellent electrical power of the material Chemical properties, suitable for efficient applications of lithium-ion batteries.

CN119181791AInactive Publication Date: 2024-12-24HUNAN NANENG TIMES TECH DEV CO LTD

Patent Information

Application Number
CN202411668332.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The preparation method of high-entropy alloy coated single crystal nickel-rich cobalt-free cathode material in the prior art is high cost, low safety, and complex in the preparation process. The traditional cladding layer affects lithium ion diffusion and cannot effectively improve the conductivity and electrochemical properties of the material. .

Method used

By solid phase sintering, nano nickel oxide, nano manganese oxide and LiOH·H2O are ground and stirred evenly with the high-entropy alloy precursor solution, and perform one-stage sintering and two-stage sintering to form a high-entropy alloy cladding layer, simplifying the preparation process. Improve the conductivity and electrochemical properties of the material.

Benefits of technology

It realizes the efficient preparation of a high-entropy alloy coated single-crystal nickel-rich cobalt-free cathode material, improves the conductivity of the material, reduces resistance, and enhances the cyclic performance and energy density of the material. It has a simple process and low cost, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181791A_ABST
    Figure CN119181791A_ABST
Patent Text Reader

Abstract

The invention relates to the field of energy storage battery materials, in particular to a high-entropy alloy coated single crystal nickel-rich cobalt-free positive electrode material and a preparation method thereof.The preparation method comprises the following steps that S1, nano nickel oxide, nano manganese oxide and LiOH.H2O are ground and mixed to be uniform, and mixed powder is obtained; s2, uniformly stirring and mixing the mixed powder and the high-entropy alloy precursor solution, performing vacuum drying, and performing first-stage sintering in an oxygen atmosphere; the high-entropy alloy precursor solution is a metal salt solution containing aluminum, titanium, molybdenum, manganese and nickel metal ions; and S3, carrying out second-stage sintering, naturally cooling to room temperature, and grinding to obtain the high-entropy alloy coated single-crystal nickel-rich cobalt-free positive electrode material. The preparation process of the high-entropy alloy coated single crystal nickel-rich cobalt-free positive electrode material is simple, the high-entropy alloy coated layer can improve the conductivity, the power and the energy density performance, the growth of primary particles can be promoted by two-stage calcination, the rate capability is excellent, and the cycle performance is stable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of energy storage battery materials, and in particular to a high entropy alloy coated single crystal nickel-rich cobalt-free positive electrode material and a preparation method thereof. Background Art

[0002] With the substantial increase in global energy consumption, the energy system needs to transform from traditional energy to clean renewable energy to cope with climate change caused by carbon emissions, and innovation in new energy core technologies is the key to promoting energy transformation. New energy materials and devices play an incomparable and important role in new energy technologies. Among them, lithium-ion batteries, with their unique energy supply methods and environmental friendliness, provide a new development path for the efficient use of renewable energy. As one of the main components of lithium-ion batteries, positive electrode materials are the key to limiting the energy density of lithium-ion batteries. Driven by the demand of the electric vehicle market, layered ternary positive electrode materials (LiNi x Co y M z O 2 , x+y+z=1, NCM) has gradually occupied a dominant position in the market with its advantages such as high energy density and long driving range. In ternary positive electrode materials, the increase of nickel content can increase the releasable capacity of the material; the presence of cobalt can inhibit the irreversible phase change of the material to a certain extent, but due to resource constraints, the price is relatively expensive. Therefore, people's demand for the comprehensive performance of long cycle mileage and low preparation cost of electric vehicles has driven the development of positive electrode materials towards high specific capacity nickel-rich, low-cost cobalt-free, and highly stable single crystal.

[0003] In the current research on the modification of single-crystal nickel-rich ternary cathode materials, there are mainly two modification schemes: doping and surface coating. Generally, doping can effectively inhibit the Li + / Ni 2+ Mixed arrangement plays a supporting role and stabilizes the bulk structure, but it cannot completely avoid the contact between the material and the electrolyte. Surface coating can avoid direct contact between the positive electrode material and the electrolyte during the cycle. At the same time, the coating layer acts as an HF scavenger to reduce the HF content in the electrolyte, thereby improving the electrochemical performance of nickel-rich materials. However, the traditional coating layer also has obstacles to Li +Diffusion, high entropy alloy coating is beneficial to improve the conductivity of the material, reduce resistance, reduce energy loss during the cycle, improve power and energy density performance, and the composite material has excellent electrochemical performance compared to traditional coating. For single crystal nickel-rich ternary materials, using high entropy alloy as a coating is an effective modification method. Patent document CN117747967A first prepares a high entropy alloy by hydrothermal reaction, obtains a high nickel ternary material by high temperature sintering, and finally coats the high entropy alloy on the surface of the high nickel ternary positive electrode material by high temperature calcination. Patent document CN118472218A deposits a high entropy alloy on the surface of a high nickel single crystal ternary positive electrode material by a hydrothermal method, washes, dries, and finally sinters to generate a nickel-rich single crystal ternary material tightly coated with a high entropy alloy. The above two inventions both involve hydrothermal reactions, which are high in cost, low in safety, and the entire preparation process is relatively complicated.

[0004] Therefore, there is currently a lack of an efficient and low-cost preparation method for high-entropy alloy-coated single crystal nickel-rich cobalt-free positive electrode material. Summary of the invention

[0005] The technical problem to be solved by the present invention is that the traditional coating layer affects the diffusion of lithium ions in the positive electrode material, overcomes the shortcomings of the prior art, and provides a high entropy alloy coated single crystal nickel-rich cobalt-free positive electrode material and a preparation method.

[0006] In order to solve the above technical problems, the technical solution proposed by the present invention is: A method for preparing a high entropy alloy coated single crystal nickel-rich cobalt-free positive electrode material comprises the following steps: S1. Mix nano nickel oxide, nano manganese oxide and LiOH·H 2 O Grind and mix evenly to obtain mixed powder; S2. The mixed powder obtained in S1 is stirred and mixed evenly with a high entropy alloy precursor solution, and then sintered in an oxygen atmosphere after vacuum drying; the high entropy alloy precursor solution is a metal salt solution including aluminum, titanium, molybdenum, manganese and nickel metal ions; S3. The sample sintered in the first stage in S2 is subjected to a second stage of sintering, naturally cooled to room temperature, and ground to obtain a single crystal nickel-rich cobalt-free positive electrode material coated with a high entropy alloy.

[0007] The present application adopts a solid-phase sintering method. In the first stage of sintering, the coating layer and the matrix material are mixed and coated and sintered to form primary particles with stable morphology, and continue to grow through the second stage of sintering to better coat the coating layer on the matrix. The preparation operation is simple and the steps are convenient. Compared with traditional coating, the obtained high-entropy alloy coating is beneficial to improving the conductivity of the material, reducing resistance, reducing energy loss during the cycle, improving power and energy density performance, and the composite material has excellent electrochemical properties.

[0008] The nano nickel oxide and nano manganese oxide of the matrix raw materials are nano-scale oxides with small particles and can react more fully; the raw materials of the mixed powder contain only nickel, manganese, lithium, oxygen and hydrogen elements. The hydrogen element will volatilize during high-temperature reaction, ensuring that the positive electrode material is free of impurities.

[0009] The molybdenum element in the coating layer can improve the hardness and strength of the high-entropy alloy, the titanium element can enhance the corrosion resistance and strength of the high-entropy alloy, the aluminum element improves the strength and hardness of the alloy, manganese and nickel are the main metal elements of the matrix material, and the positive electrode material product prepared by coating has high strength, low impedance and excellent performance.

[0010] Preferably, the molar ratio of nano nickel oxide to nano manganese oxide in S1 is (90-95): (5-10).

[0011] Preferably, the nano nickel oxide, nano manganese oxide and LiOH·H 2 The lithium ratio of O is (1.05-1.20): 1. The lithium ratio refers to the molar ratio of Li to the total precursor raw materials.

[0012] Preferably, the grinding in S1 is ball milling, and the ball milling mixing time is 4 to 16 h. 2 The mass ratio of the mixture of O and the mass of the ball milling beads is 1:(5~20), and the ball milling mixing speed is 200~800rpm.

[0013] Preferably, the molar ratio of aluminum, titanium, molybdenum, manganese and nickel in the high entropy alloy precursor solution in S2 is 1:1:1:(1-2):(1-5). By preparing equal or nearly equal amounts of multiple metal elements, the requirements for preparing a high entropy alloy precursor can be met.

[0014] Preferably, the mass solid-liquid ratio of the mixed powder to the high entropy alloy precursor solution in S2 is 1:(5-20), the stirring is magnetic stirring, the stirring time is 4-12 h, the vacuum drying temperature is 40-80°C, and the drying time is 8-24 h.

[0015] Preferably, the flow rate of oxygen in the oxygen atmosphere in S2 is 50-200 sccm, the temperature of the first stage sintering is 450-650° C., and the holding time is 8-16 h.

[0016] Preferably, the heating rate of the two-stage sintering in S3 is 2-20°C / min, the sintering temperature is 700-950°C, and the holding time is 8-24 h. The two-stage calcination can promote the growth of primary particles while taking into account the dispersibility of secondary particles, and control the morphology and size of the high-entropy alloy-coated single crystal nickel-rich cobalt-free positive electrode material.

[0017] Under the same technical concept, the present invention also provides a high-entropy alloy-coated single crystal nickel-rich cobalt-free positive electrode material prepared by the preparation method. The positive electrode material is based on a single crystal nickel-rich cobalt-free material, and a high-entropy alloy is coated on the base. The mass ratio of the high-entropy alloy to the single crystal nickel-rich cobalt-free base is (1:100~500).

[0018] Preferably, the positive electrode material is micron-sized block particles with an average diameter of 2 to 5 μm.

[0019] Compared with the prior art, the advantages of the present invention are: (1) The high entropy alloy coated single crystal nickel-rich cobalt-free positive electrode material of the present invention has a nickel-rich cobalt-free single crystal material as a matrix and a high entropy alloy as a coating layer, wherein the nickel-rich cobalt-free material is nano-nickel oxide, nano-manganese oxide and LiOH·H 2 O is formed by the reaction, and the coating layer high entropy alloy is a metal mixture of aluminum, titanium, molybdenum, manganese, nickel, etc. The positive electrode material of the present invention can effectively improve the conductivity of the material, reduce resistance, reduce energy loss during the cycle, improve power and energy density performance, have excellent rate performance, and stable cycle performance.

[0020] (2) The high-entropy alloy-coated single crystal nickel-rich cobalt-free positive electrode material of the present invention has a simple preparation process. The high-entropy alloy of the coating layer can improve conductivity, reduce resistance, reduce energy loss during the cycle, and improve power and energy density performance. The two-stage calcination can promote the growth of primary particles, and the rate performance is excellent and the cycle performance is stable. The overall preparation adopts high-temperature sintering, does not contain toxic solvents, is green and environmentally friendly, and is in line with the concept of green and sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the SEM spectrum of the high entropy alloy-coated single crystal nickel-rich cobalt-free positive electrode material in Example 1 of the present invention.

[0022] Figure 2 This is the first charge and discharge diagram of button-type batteries assembled with the pole pieces obtained in Example 1 of the present invention and Comparative Example 1.

[0023] Figure 3 It is a comparison chart of the cycle performance of button-type batteries assembled with the pole pieces obtained in Example 1 of the present invention and in Comparative Example 1. DETAILED DESCRIPTION

[0024] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0025] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0026] Unless otherwise specified, all reagents and raw materials used in the present invention are commercially available products or products that can be prepared by known methods.

[0027] Embodiment 1: A high entropy alloy coated single crystal nickel-rich cobalt-free positive electrode material HEA (AlTiMoMnNi) @ LiNi 0.9 Mn 0.1 O 2 , including a nickel-rich cobalt-free matrix and a high-entropy alloy coating layer, wherein the molar ratio of nickel to manganese in the nickel-rich cobalt-free matrix is ​​0.9:0.1, the lithium ratio Li / TM (the molar ratio of Li to the total precursor raw material) is 1.05:1, and the high-entropy alloy HEA (AlTiMoMnNi) of the coating layer is an alloy with a molar ratio of aluminum, titanium, molybdenum, manganese, and nickel of 1:1:1:2:5, and the particle size of the positive electrode material is 3 μm. In the positive electrode material, the mass of the high-entropy alloy is 0.04 g, and the mass of the single-crystal nickel-rich cobalt-free matrix is ​​10 g.

[0028] Figure 1 This is the SEM spectrum of the high entropy alloy-coated single crystal nickel-rich cobalt-free positive electrode material in Example 1 of the present invention.

[0029] The method for preparing the high entropy alloy coated single crystal nickel-rich cobalt-free positive electrode material in this embodiment comprises the following steps: (1) Weigh 6.76 g of nano nickel oxide, 0.87 g of nano manganese oxide, and 4.41 g of LiOH·H 2 O was mixed by ball milling according to a lithium ratio of Li / TM of 1.05:1, a ratio of the mass of the mixture to the mass of the ball milling beads of 1:20, a ball milling mixing time of 16 h, a ball milling mixing speed of 200 rpm, and the ball milling mixing was uniform to obtain a mixed powder.

[0030] (2) The mixed powder obtained in step (1) was immersed in aluminum chloride, titanium oxalate, molybdenum nitrate, manganese sulfate, and nickel nitrate dissolved in deionized water (metal salt solution is 0.05 mol / L) in a solid-liquid ratio of 1:5, magnetically stirred for 12 h, mixed evenly, vacuum filtered and washed several times, and placed in a vacuum drying oven at 80°C for 8 h.

[0031] The dry mixed sample was placed in an alumina boat and kept at 4 °C. 2 The sintering is carried out in a tube furnace with an atmosphere of O 2The atmosphere flow rate was 50 sccm, the calcination temperature was 450 °C, and the holding time was 8 h.

[0032] (3) On the basis of step (2), a two-stage calcination is carried out, with a heating rate of 5°C / min, a sintering temperature of 850°C, and a holding time of 12 h. The product is taken out and ground to obtain a high-entropy alloy-coated single crystal nickel-rich cobalt-free positive electrode material.

[0033] Embodiment 2: A high entropy alloy coated single crystal nickel-rich cobalt-free positive electrode material HEA (AlTiMoMnNi) @ LiNi 0.92 Mn 0.08 O 2 , including a nickel-rich cobalt-free matrix and a high-entropy alloy coating layer, wherein the molar ratio of nickel to manganese in the nickel-rich cobalt-free matrix is ​​0.92:0.08, the lithium ratio Li / TM is 1.10:1, the high-entropy alloy HEA (AlTiMoMnNi) of the coating layer is an alloy with a molar ratio of aluminum, titanium, molybdenum, manganese and nickel elements of 1:1:1:1:1, and the particle size of the positive electrode material is 2 μm. In the positive electrode material, the mass of the high-entropy alloy is 0.02 g, and the mass of the single-crystal nickel-rich cobalt-free matrix is ​​10 g.

[0034] The method for preparing the high entropy alloy coated single crystal nickel-rich cobalt-free positive electrode material in this embodiment comprises the following steps: (1) Weigh 6.87 g of nano nickel oxide, 0.70 g of nano manganese oxide, and 4.61 g of LiOH·H 2 O was mixed by ball milling according to the lithium ratio Li / TM of 1.10:1, the mass ratio of the mixture to the mass of the ball milling beads was 1:15, the milling time was 12 h, the ball milling speed was 300 rpm, and the ball milling was uniform to obtain a mixed powder.

[0035] (2) The mixed powder obtained in step (1) was immersed in aluminum chloride, titanium oxalate, molybdenum nitrate, manganese sulfate, and nickel nitrate dissolved in deionized water in a molar ratio of 1:1:1:1:1 (the metal salt solution is 0.06 mol / L) at a solid-liquid ratio of 1:8, and magnetically stirred for 8 h. The mixture was mixed evenly, vacuum filtered and washed several times, and dried in a vacuum drying oven at 60°C for 12 h.

[0036] The above dry mixed sample was placed in an alumina boat and 2 The sintering is carried out in a tube furnace with an atmosphere of O 2 The atmosphere flow rate was 70 sccm, the calcination temperature was 500 °C, and the holding time was 12 h.

[0037] (3) On the basis of step (2), a two-stage calcination is carried out, with a heating rate of 2°C / min, a sintering temperature of 900°C, and a holding time of 8 h. The product is taken out and ground to obtain a high-entropy alloy-coated single crystal nickel-rich cobalt-free positive electrode material.

[0038] Embodiment 3: A high entropy alloy coated single crystal nickel-rich cobalt-free positive electrode material HEA (AlTiMoMnNi) @ LiNi 0.94 Mn 0.06 O 2 , including a nickel-rich cobalt-free matrix and a high-entropy alloy coating layer, wherein the molar ratio of nickel to manganese in the nickel-rich cobalt-free matrix is ​​0.94:0.06, the lithium ratio Li / TM is 1.15:1, the high-entropy alloy HEA (AlTiMoMnNi) of the coating layer is an alloy with a molar ratio of aluminum, titanium, molybdenum, manganese and nickel elements of 1:1:1:1:2, and the particle size of the positive electrode material is 4μm. In the positive electrode material, the mass of the high-entropy alloy is 0.06 g, and the mass of the single-crystal nickel-rich cobalt-free matrix is ​​10 g.

[0039] A high entropy alloy coated single crystal nickel-rich cobalt-free positive electrode material HEA@SC-NM of the present invention comprises a nickel-rich cobalt-free and a coating layer high entropy alloy, wherein the nickel-rich cobalt-free is nano nickel oxide, nano manganese oxide and LiOH·H in a molar ratio of 0.94:0.06. 2 O is a product formed by a reaction with a lithium ratio of Li / TM of 1.15:1, the coating layer high entropy alloy is a reaction product with a molar ratio of aluminum, titanium, molybdenum, manganese and nickel of 1:1:1:1:2, and the particle size of the positive electrode material is 4μm.

[0040] The method for preparing the high entropy alloy coated single crystal nickel-rich cobalt-free positive electrode material in this embodiment comprises the following steps: (1) Weigh 7.02 g of nano nickel oxide, 0.52 g of nano manganese oxide, and 4.82 g of iOH·H 2 O was mixed by ball milling according to the lithium ratio Li / TM of 1.15:1, the mass ratio of the mixture to the mass of the ball milling beads was 1:10, the mixing time was 10 h, the mixing speed of the ball milling was 400 rpm, and the ball milling was uniform to obtain a mixed powder.

[0041] (2) The mixed powder obtained in step (1) was immersed in aluminum chloride, titanium oxalate, molybdenum nitrate, manganese sulfate, and nickel nitrate dissolved in deionized water (metal salt solution is 0.03 mol / L) in a solid-liquid ratio of 1:10, magnetically stirred for 10 h, mixed evenly, vacuum filtered and washed several times, and placed in a vacuum drying oven at 70°C for 16 h.

[0042] The above dry mixed sample was placed in an alumina boat and 2The first stage sintering was carried out in an atmosphere tube furnace with an O2 atmosphere flow rate of 100 sccm, a calcination temperature of 450°C, and a holding time of 16 h.

[0043] (3) Based on step (2), a two-stage calcination is carried out with a heating rate of 10°C / min, a sintering temperature of 950°C, and a holding time of 16 h. The product is taken out and ground to obtain a high-entropy alloy-coated single crystal nickel-rich cobalt-free positive electrode material.

[0044] Embodiment 4: A high entropy alloy coated single crystal nickel-rich cobalt-free positive electrode material HEA (AlTiMoMnNi) @ LiNi 0.95 Mn 0.05 O 2 , including a nickel-rich cobalt-free matrix and a high-entropy alloy coating layer, wherein the molar ratio of nickel to manganese in the nickel-rich cobalt-free matrix is ​​0.95:0.05, the lithium ratio Li / TM is 1.05:1, the high-entropy alloy of the coating layer is an alloy with a molar ratio of aluminum, titanium, molybdenum, manganese and nickel of 1:1:1:1:3, and the particle size of the positive electrode material is 5 μm. In the positive electrode material, the mass of the high-entropy alloy is 0.08 g, and the mass of the single crystal nickel-rich cobalt-free matrix is ​​10 g.

[0045] A high entropy alloy coated single crystal nickel-rich cobalt-free positive electrode material HEA (AlTiMoMnNi) @ LiNi 0.95 Mn 0.05 O 2 , including nickel-rich cobalt-free and coating layer high entropy alloy, wherein the nickel-rich cobalt-free is nano nickel oxide, nano manganese oxide and LiOH·H in a molar ratio of 0.95:0.05 2 O is a product formed by reaction according to a lithium ratio Li / TM of 1.05:1, the coating layer high entropy alloy HEA (AlTiMoMnNi) is a reaction product of aluminum, titanium, molybdenum, manganese, and nickel elements in a molar ratio of 1:1:1:1:3, and the particle size of the positive electrode material is 5μm.

[0046] The method for preparing the high entropy alloy coated single crystal nickel-rich cobalt-free positive electrode material in this embodiment comprises the following steps: (1) Weigh 7.10 g of nano nickel oxide, 0.44 g of nano manganese oxide, and 4.41 g of iOH·H 2 O was mixed by ball milling according to the lithium ratio Li / TM of 1.05:1, the mass ratio of the mixture to the mass of the ball milling beads was 1:8, the milling mixing time was 8 h, the ball milling mixing speed was 600 rpm, and the ball milling mixing was uniform to obtain a mixed powder.

[0047] (2) The mixed powder obtained in step (1) was immersed in aluminum chloride, titanium oxalate, molybdenum nitrate, manganese sulfate, and nickel nitrate dissolved in deionized water (metal salt solution is 0.04 mol / L) in a solid-liquid ratio of 1:12, magnetically stirred for 18 h, mixed evenly, vacuum filtered and washed several times, and placed in a vacuum drying oven at 80°C for 20 h.

[0048] The dried mixed sample was placed in an alumina boat and sintered in an O2 atmosphere tube furnace. 2 The atmosphere flow rate was 120 sccm, the calcination temperature was 550 °C, and the holding time was 10 h.

[0049] (3) Based on step (2), a two-stage calcination is carried out with a heating rate of 4°C / min, a sintering temperature of 750°C, and a holding time of 20 h. The product is taken out and ground to obtain a high-entropy alloy-coated single crystal nickel-rich cobalt-free positive electrode material.

[0050] Embodiment 5: A high entropy alloy coated single crystal nickel-rich cobalt-free positive electrode material HEA (AlTiMoMnNi) @ LiNi 0.93 Mn 0.07 O 2 , including a nickel-rich cobalt-free matrix and a high-entropy alloy coating layer, wherein the molar ratio of nickel to manganese in the nickel-rich cobalt-free matrix is ​​0.93:0.07, the lithium ratio Li / TM is 1.10:1, the high-entropy alloy HEA (AlTiMoMnNi) of the coating layer is an alloy with a molar ratio of aluminum, titanium, molybdenum, manganese and nickel of 1:1:1:1:4, and the particle size of the positive electrode material is 3 μm. In the positive electrode material, the mass of the high-entropy alloy is 0.10 g, and the mass of the single-crystal nickel-rich cobalt-free matrix is ​​10 g.

[0051] The method for preparing the high entropy alloy coated single crystal nickel-rich cobalt-free positive electrode material in this embodiment comprises the following steps: (1) Weigh 6.95 g of nano nickel oxide, 0.61 g of nano manganese oxide, and 4.61 g of iOH·H 2 O was mixed by ball milling according to the lithium ratio Li / TM of 1.10:1, the mass ratio of the mixture to the mass of the ball milling beads was 1:5, the milling time was 6 h, the ball milling speed was 800 rpm, and the ball milling was uniform to obtain a mixed powder.

[0052] (2) The mixed powder obtained in step (1) was immersed in aluminum chloride, titanium oxalate, molybdenum nitrate, manganese sulfate, and nickel nitrate dissolved in deionized water (metal salt solution is 0.08 mol / L) in a solid-liquid ratio of 1:15, and magnetically stirred for 8 h. The mixture was mixed evenly, vacuum filtered and washed several times, and dried in a vacuum drying oven at 70°C for 12 h.

[0053] The above-mentioned dry mixed sample was placed in an alumina ark and sintered in an O2 atmosphere tube furnace. The O2 atmosphere flow rate was 150 sccm, the calcination temperature was 500°C, and the holding time was 14 h.

[0054] (3) Based on step (2), a two-stage calcination is carried out with a heating rate of 15°C / min, a sintering temperature of 800°C, and a holding time of 24 h. The product is taken out and ground to obtain a high-entropy alloy-coated single crystal nickel-rich cobalt-free positive electrode material.

[0055] Comparative Example 1: The single crystal nickel-rich cobalt-free positive electrode material in this comparative example differs from that in Example 1 only in that it does not contain a high-entropy alloy coating layer, wherein the positive electrode material is only a single crystal nickel-rich cobalt-free high-entropy alloy without a coating layer, and the preparation process is the same as the preparation process conditions in Example 1.

[0056] Comparative Example 2: A high entropy alloy coated single crystal nickel-rich positive electrode material HEA (AlTiMoMnNi) @ LiNi 0.93 Co 0.02 Mn 0.05 O 2 , including a nickel-rich matrix and a high-entropy alloy coating layer, wherein the molar ratio of nickel, manganese and cobalt in the nickel-rich matrix is ​​0.93:0.05:0.02, the lithium ratio Li / TM is 1.05:1, the high-entropy alloy HEA (AlTiMoMnNi) of the coating layer is an alloy with a molar ratio of aluminum, titanium, molybdenum, manganese and nickel elements of 1:1:1:2:5, and the particle size of the positive electrode material is 3 μm. In the positive electrode material, the mass of the high-entropy alloy is 0.04 g, and the mass of the single-crystalline nickel-rich matrix is ​​10 g.

[0057] The method for preparing the high entropy alloy coated single crystal nickel-rich cobalt-free positive electrode material in this embodiment comprises the following steps: (1) Weigh 6.95 g of nano nickel oxide, 0.40 g of nano cobalt oxide, 0.17 g of nano manganese oxide, and 4.61 g of iOH·H 2 O was mixed by ball milling according to the lithium ratio Li / TM of 1.05:1, the mass ratio of the mixture to the mass of the ball milling beads was 1:20, the mixing time was 16 h, the mixing speed of the ball milling was 200 rpm, and the ball milling was uniform to obtain a mixed powder.

[0058] (2) The mixed powder obtained in step (1) was immersed in aluminum chloride, titanium oxalate, molybdenum nitrate, manganese sulfate, and nickel nitrate dissolved in deionized water (metal salt solution is 0.05 mol / L) in a solid-liquid ratio of 1:5, magnetically stirred for 12 h, mixed evenly, vacuum filtered and washed several times, and placed in a vacuum drying oven at 80°C for 8 h.

[0059] (3) Place the dry mixed sample in an alumina boat and 2 The sintering is carried out in a tube furnace with an atmosphere of O 2 The atmosphere flow rate was 50 sccm, the calcination temperature was 450 °C, and the holding time was 8 h.

[0060] (4) Based on step (3), a two-stage calcination is carried out with a heating rate of 5°C / min, a sintering temperature of 850°C, and a holding time of 12 h. The material is taken out and ground to obtain a high-entropy alloy-coated single crystal nickel-rich positive electrode material.

[0061] Comparative Example 3: A high entropy alloy coated single crystal nickel-rich cobalt-free cathode material HEA(AlTiMoMnNi)@LiNi 0.9 Mn 0.1 O 2 , including a nickel-rich cobalt-free matrix and a high-entropy alloy coating layer, wherein the molar ratio of nickel to manganese in the nickel-rich cobalt-free matrix is ​​0.9:0.1, the lithium ratio Li / TM is 1.05:1, the high-entropy alloy HEA (AlTiMoMnNi) of the coating layer is an alloy with a molar ratio of aluminum, titanium, molybdenum, manganese and nickel of 1:1:1:2:5, and the particle size of the positive electrode material is 3 μm. In the positive electrode material, the mass of the high-entropy alloy is 0.04 g, and the mass of the single-crystal nickel-rich cobalt-free matrix is ​​10 g.

[0062] The method for preparing the high entropy alloy coated single crystal nickel-rich cobalt-free positive electrode material in this embodiment comprises the following steps: (1) Weigh 6.76 g of nano nickel oxide, 0.87 g of nano manganese oxide, and 4.41 g of LiOH·H 2 O was mixed by ball milling according to a lithium ratio of Li / TM of 1.05:1, a ratio of the mass of the mixture to the mass of the ball milling beads of 1:20, a ball milling mixing time of 16 h, a ball milling mixing speed of 200 rpm, and the ball milling mixing was uniform to obtain a mixed powder.

[0063] (2) The mixed powder obtained in step (1) was immersed in aluminum chloride, titanium oxalate, molybdenum nitrate, manganese sulfate, and nickel nitrate dissolved in deionized water (metal salt solution is 0.05 mol / L) in a solid-liquid ratio of 1:5, magnetically stirred for 12 h, mixed evenly, vacuum filtered and washed several times, and placed in a vacuum drying oven at 80°C for 8 h.

[0064] The dry mixed sample was placed in an alumina boat and kept at 4 °C. 2 Sintering was carried out in a tubular furnace with an atmosphere of O 2 The atmosphere flow rate is 50 sccm, the heating rate is 5°C / min, the sintering temperature is 850°C, the holding time is 12 h, and the sintered product is taken out and ground to obtain a high entropy alloy-coated single crystal nickel-rich cobalt-free positive electrode material.

[0065] It is difficult to produce single-crystal NCM materials with high purity by simply calcining at high temperature in one stage. The two-stage calcination procedure can form larger single crystal particles while preventing Li 5 MnO 4 The formation of lithium is carried out by adding lithium at a lower calcination temperature and secondary calcination is carried out to make up for the lack of lithium in the single crystal material.

[0066] The high entropy alloy-coated single crystal nickel-rich positive electrode materials prepared in the above examples and comparative examples were used as positive electrode materials for button cells and assembled into button cells for battery testing. Figure 2 The first charge and discharge diagram of the button cell assembled with the electrode pieces obtained in Example 1 of the present invention and Comparative Example 1. Under the conditions of a discharge cut-off voltage of 2.0 V and a charge cut-off voltage of 4.3 V, after three cycles of activation at 0.1C, the reversible specific capacity and the first coulombic efficiency values ​​of the 0.5C charge and 0.5C discharge are shown in Table 1. The test results of 100 cycles are shown in Table 1. Figure 2 As shown, Figure 3 This is a comparison chart of the cycle performance of button-type batteries assembled with the pole pieces obtained in Example 1 of the present invention and in Comparative Example 1. The capacity retention rate of the button-type battery in Example 1 after 100 cycles is 76.22%, and the reversible specific capacity can reach 220.96 mAh / g. However, the capacity retention rate of the button-type battery in Comparative Example 1 after 100 cycles is only 49.60%, and the reversible specific capacity can reach 212.81 mAh / g. Table 1 Electrochemical performance of each embodiment and comparative example

[0067] It can be seen from the test data in Table 1 that only the high entropy alloy-coated single crystal nickel-rich cobalt-free material of the present invention can alleviate the occurrence of side reactions, improve conductivity, and improve the first-cycle coulombic efficiency and reversible specific capacity of the positive electrode material.

[0068] The high entropy alloy coated single crystal nickel-rich positive electrode material provided in the above embodiment of the present invention has a simple process, low cost, and is suitable for large-scale production. The material obtained by the process is conducive to improving the conductivity of the material, reducing resistance, reducing energy loss during the cycle, improving power and energy density performance, and the composite material has excellent electrochemical performance. The positive electrode material obtained by the preparation method provided by the embodiment of the present invention has a high reversible capacity, excellent rate performance, stable cycle performance, and good safety performance. It can be used not only in portable electronic devices, but also in the field of electric vehicles.

Claims

1. A method for preparing a high entropy alloy coated single crystal nickel-rich cobalt-free positive electrode material, characterized in that: The following steps are involved: S1. Grind and mix nano nickel oxide, nano manganese oxide and LiOH·H2O to obtain a mixed powder; S2. The mixed powder obtained in S1 is stirred and mixed evenly with a high entropy alloy precursor solution, and after vacuum drying, a sintering step is performed in an oxygen atmosphere, wherein the sintering temperature is 450-650°C and the holding time is 8-16 h; the high entropy alloy precursor solution is a metal salt solution comprising aluminum, titanium, molybdenum, manganese and nickel metal ions; the molar ratio of aluminum, titanium, molybdenum, manganese and nickel in the high entropy alloy precursor solution is 1:1:1:(1-2):(1-5); S3. The sample sintered in the first stage in S2 is subjected to a second stage of sintering, naturally cooled to room temperature, and ground to obtain a high-entropy alloy-coated single crystal nickel-rich cobalt-free positive electrode material.

2. The preparation method according to claim 1, characterized in that The molar ratio of nano nickel oxide to nano manganese oxide in S1 is (90-95): (5-10).

3. The preparation method according to claim 1, characterized in that: The lithium ratio of nano nickel oxide, nano manganese oxide and LiOH·H2O described in S1 is (1.05~1.20):

1.

4. The preparation method according to claim 1, characterized in that: The grinding described in S1 is ball milling, the ball milling mixing time is 4-16 h, the mass ratio of the mixture of nano-nickel oxide, nano-manganese oxide and LiOH·H2O to the mass of ball milling beads is 1:(5-20), and the ball milling mixing speed is 200-800 rpm.

5. The preparation method according to claim 1, characterized in that: The mass solid-liquid ratio of the mixed powder to the high entropy alloy precursor solution in S2 is 1:(5~20), the stirring is magnetic stirring, the stirring time is 4~12 h, the vacuum drying temperature is 40~80°C, and the drying time is 8~24 h.

6. The preparation method according to claim 1, characterized in that: The flow rate of oxygen in the oxygen atmosphere in S2 is 50-200 sccm.

7. The preparation method according to claim 1, characterized in that: The heating rate of the second-stage sintering in S3 is 2~20℃ / min, the sintering temperature is 700~950℃, and the holding time is 8~24h.

8. A high entropy alloy coated single crystal nickel-rich cobalt-free positive electrode material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The positive electrode material is based on a single crystal nickel-rich cobalt-free material, on which a high entropy alloy is coated, and the mass ratio of the high entropy alloy to the single crystal nickel-rich cobalt-free matrix is ​​1:(100-500).

9. The high entropy alloy coated single crystal nickel-rich cobalt-free positive electrode material according to claim 8, characterized in that: The positive electrode material is micron-sized block particles with an average diameter of 2-5 μm.

Citation Information

Patent Citations

  • High-nickel ternary cathode material coated with fast ion conductor and preparation method thereof

    CN110690435A

  • Single-crystal battery positive electrode material and preparation method thereof

    CN113437260A

  • High-entropy ceramic modified positive electrode material and preparation method and application thereof

    CN115050940A

  • High-entropy oxide coated positive electrode material as well as preparation method and application thereof

    CN117401730A

  • Ternary positive electrode material, preparation method thereof and lithium ion battery

    CN117976886A

Cited By

  • Distributed cobalt-free high-entropy energy storage electrode and preparation method and application thereof

    CN120184177A

  • Double-doped single-crystal ultrahigh-nickel positive electrode material as well as preparation method and application thereof

    CN120210929A

  • High-entropy alloy coated ternary material as well as preparation method and application thereof

    CN120749144A